Effect of different high-fat diets on lipid profile in albino rats - Nwokoro, Chukwuemeka Pius; Olawale, Ajuwon (Covenant Journal of Physical and Life Sciences, 2025)
Abstract: High-fat diets and sedentary lifestyles are the main causes of obesity, which is a major risk factor for chronic illnesses like heart disease, high blood pressure, type 2 diabetes, chronic kidney disease, and several types of cancer. This comparative study examines how male albino rats' lipid profiles are affected by high-fat diets made from widely eaten vegetable oils. A total of 48 male albino rats weighing between 100 and 150 grams were randomly assigned to five groups of eight. As the control group, Group 1 was given a diet that contained 11% energy from 5% soybean oil. Rats in Group 2 were given a diet that contained 30% crude palm oil and 2.5% soybean oil (CPO group). Rats in Group 3 were given a diet that contained 30% refined palm oil and 2.5% soybean oil (RPO group). Rats in groups 2–5 were fed a diet consisting of 2.5% soybean oil and 30% groundnut oil (GO group) and Group 5 rats were fed a diet consisting of 2.5% soybean oil and 30% shea butter (SHB group). Blood samples were taken at the end of the 8-week feeding protocol in order to evaluate lipid profiles, and the atherogenic index and coronary risk index were also computed. The results indicated that there were no significant differences (p < 0.05) in the levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, or high-density lipoprotein cholesterol between the rats fed high-fat diets and the control group. In conclusion, the high-fat meals assessed in this study did not negatively impact the rats' lipid profiles and fared similarly to soybean oil.